Komunikasi Sosial Komunitas Adat Bayan Lombok Utara: Studi Etnografi Model Komunikasi Tradisi Menyilaq - Kadri, Kadri (Jurnal Komunikasi Islam, 2018)
This paper analyses the social communication model of a menyilaq ritual within the Bayan indigenous people in North Lombok, West Nusa Tenggara (NTB). By using the ethnographic communication approach, this study found that the tradition of menyilaq carried out by Pebenkel to the Bayan indigenous people utilised the patterns of passive top-down and active top-down socialization. The Menyilaq ritual reflected effective communication as there were personal contact and immediate feedback within both top-down socialisation models. Additionally, it became a medium of communication of silaturahim which were considered as a form of respects to maintain family ties and able to build good relations among community members. Further, the tradition has shown its consistency in maintaining the tradition of information delivery amid the onslaught of the current communication technology.